Serum calcium and phosphorus levels: a marker of disease activity in senile cataract patients - Deokar, Smita A.; Rai, Pooja S. K.; Rai, Anita B.; Sudarshan, .; Sundharan, Shimi; Bakshi, Amruta A. (International Journal of Advances in Medicine, 2018)
Background: The present study was aimed to study alterations in serum levels of calcium and phosphorus levels in senile cataract patients. Methods: 25 senile cataract patients in age group of 50 to 80 years and 25 control group were included in the study. Serum Calcium and Phosphorus levels were determined by Orthocresolphthalein, Fiske SubbaRow method respectively Results: Significantly increased levels of serum calcium in cataract patients (11.58±1.65 mg/dl) were found as compared to controls (8.53±1.45mg/dl) (p<0.0001). Serum phosphorus concentration in cataract patients (5.28±0.46 mg/dl) were significantly increased when compared to controls (3.02±1.23mg/dl) (p<0.0001). Conclusions: Presence of G-protein receptors in lens leads to the release of intracellular calcium. As total calcium in the lens increases, we hypothesize that higher intercellular calcium concentrations, coupled with decreased Ca2+-ATPase activity and greater membrane permeability could lead to elevated free intracellular calcium levels causing cataract. So, abnormal elevation of serum calcium and phosphorus can be used as a marker for prevention of age-related human cataract.